REVEALING A JAVANESE IDENTITY OF PRAYER IN THE WEDHATAMA THROUGH SEMANTIC PROPOSITION - Indhiarti, Tantri Refa; Budi, Sri Utami; Winarni, Indah (Universitas Muhammadiyah Surakarta, 2017)
TheÂ Wedhatama,Â aÂ JavaneseÂ literaryÂ workÂ byÂ theÂ KingÂ MangkunegaraÂ IVÂ containsÂ philosophicalÂ teachingsÂ whichÂ areÂ quiteÂ influentialÂ inÂ ethical life.Â ThisÂ paperÂ aimsÂ at discovering the hidden meaning of the teachings which revealÂ anÂ esotericÂ knowledgeÂ ofÂ worshippingÂ inÂ termsÂ ofÂ itsÂ semanticÂ pointÂ of view.Â ThisÂ meaningÂ isÂ knownÂ throughÂ analyticÂ andÂ syntheticÂ propositionsÂ in Gambuh canto associated with 4 different types of worship. Thus, the qualitative paradigm is used in which the data were obtained through library research. In thisÂ study,Â theÂ syntheticÂ propositionÂ shows theÂ breadthÂ ofÂ theÂ poetâsÂ signifying esoteric intentionÂ thatÂ is about Javanese identity ofÂ prayer. ItÂ isÂ revealedÂ that theÂ fourÂ typesÂ ofÂ worshipÂ âsembahÂ raga,Â cipta,Â jiwa,Â andÂ rasaÂ âareÂ saidÂ to coincide with what are usually referred to in Muslim Sufism as syariat.Â Keywords: Gambuh canto, the Wedhatama, Javanese identity of prayer, semantic propositionÂ